DOCUMENTARY VS. ARTISTIC BIRTH PHOTOGRAPHY: TECHNIQUES FOR EFFECTIVE STORYTELLING - Liashenko, Yana (SWorldJournal, 2025)
The growing demand for both artistic and documentary birth photography, particularly in home birth settings, highlights the need to explore the specifics of this genre from both technical and conceptual perspectives. The visualization of this unique momen